Compliance with the Legal Provision of Tobacco Products in Nepal - Dhimal, Meghnath; Khatri, Bishal Dahal; Basnet, Man Bahadur; Ghimire, Sailaja; Ghimire, Namita; Acharya, Astha; Rana, Nisha; Joshi, Pramod (Journal of Nepal Health Research Council, 2025)
Background: The tobacco epidemic is one of the major threats to public health, causing nearly 8 million deaths annually worldwide. In Nepal, every year, several Nepalese people die from tobacco-related diseases illnesses. Despite the implementation of several policies and strategies, tobacco use remains prevalent. This study, thus, aims to assess compliance with the legal provisions regulating tobacco products in Kathmandu Valley. Methods: A multimethod study design was adopted to explore compliance with the legal provision of tobacco products in the Kathmandu Valley. Three hundred and five public places within the Kathmandu Valley were observed using the observation checklist, and fourteen key informant interviews were conducted. The ethical approval was obtained from the Ethical Review Board of the Nepal Health Research Council. Results: Our findings show that the average adherence to the Tobacco Product Control Act in the Kathmandu Valley was merely 33.1%. Public transportation exhibited highest compliance 53.2%, whereas eateries demonstrated the lowest compliance at 15.9%. Health organizations demonstrated the highest adherence to prohibiting indoor smoking (94.7%), although the presence of “No Smoking” signage was inadequate, varying from 1.9% to 22.7% across various locations. Conclusions: In conclusion, compliance with the legal provision of tobacco products was observed owing to limited knowledge of stakeholders, inadequate multi-sectoral coordination, and lack of monitoring mechanisms in public areas. Whereas awareness initiatives through diverse communication channels are found effective in improving compliance. Keywords: Compliance; legal provision; Nepal; public places; tobacco products.